The everyday lives of sex workers in the Netherlands - Gregory, Katherine (New approaches in sociology, 2005)
Changing perspectives on prostitution -- Finding my way into the field -- Space and place : in the windows -- Space and place : in the zone -- Victoria van der Way -- Coping strategies for economic, physical, and emotional survival on the streets and in the windows